Extract from Curcuma longa L. triggers the sunflower immune system and induces defence-related genes against Fusarium root rot - ALSAHLI, Abdulaziz; ALARAIDH, Ibrahim; RASHAD, Younes; ABDEL RAZIL, Elsayed (Phytopathologia Mediterranea, 2018)
Sunflower (Helianthus annuus L.) has economic value worldwide Fusarium root rot, caused by Fusarium solani (Mart.) Sacc., is the most important disease in sunflower crops, causing considerable economic losses. Seed treatment with a turmeric aqueous extract was tested for control of Fusarium root rot. Gas chromatography-mass spectrometry analysis of the extract identified three major constituents; ar-curcumin, camphor and α-turmerone. The greenhouse experiment showed that incidence and severity of sunflower root rot were significantly reduced after treatment with turmeric extract. Plant growth parameters also increased 2 and 4 weeks after inoculation. In addition, treatment with turmeric extract triggered the sunflower immune system, as indicated by the induction of host phenolic content and activity of antioxidant enzymes (peroxidase and phenylalanine ammonia lyase). Differential display-PCR of the treated plants showed distinct profiles of gene expression in response to the treatments. Of the four bands randomly selected for sequencing and identification, three up-regulated genes that encode defence-related proteins (glutathione S-transferase 6, ascorbate peroxidase, and defensin) were detected. A time-course real-time quantitative PCR was carried out on mRNA of the defence-related genes defensin and chitinase of the treated sunflower seedlings. After 14 d, treatment with turmeric extract enhanced the expression levels of chitinase by > nine-fold and defensin genes by > four-fold. Based on these results, we recommend treatment of sunflower seeds with turmeric extract as a disease management method against Fusarium root rot.